Social development : relationships in infancy, childhood, and adolescence - Rosen, Lisa H.; Underwood, Marion K. (Guilford Press, 2011)
This authoritative, engaging text examines the key role of relationships in child and adolescent development, from the earliest infant caregiver transactions to peer interactions, friendships, and romantic partnerships. Following the sequence of a typical social development course, sections cover foundational developmental science, the self and relationships, social behaviors, contexts for social development, and risk and resilience. Leading experts thoroughly review their respective areas and highlight the most compelling current issues, methods, and research directions. End-of-chapter suggested reading lists direct students and instructors to exemplary primary sources on each topic